A graph mining-based approach to analyze the dynamics of the Twitter community of COVID-19 misinformation disseminators - Hussna, Asma Ul (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Computer Science, 2024.